Leadership 4.0 In technical and vocational education and training institution - Wan Muda, Wan Hanim Nadrah; Ab Halim, Fazlinda; Isa, Khairunesa; Md Nasir, Ahmad Nabil (2021)
Technical and Vocational Education and Training (TVET) Institution play an important role in preparing youth to enter the workforce and in improving their employability throughout their careers. Position as a leader in TVETinstitution in new challenging stream world needs to understand the strategic role that can contribute to the growth of knowledge and skills.The systematic review method was used to synthesis of leadership concepts. Thirteen journals from various sources had been selected in this study to analyze the leadership in TVET. This study shows that innovative behavior in organizations towards different interest groups depends on the ability of organizational leadership. Through this analysis, four components have been identified that must be possessed by qualified leaders, namely style, characteristics, competencies, and ability. The results of this study showed that the dimension of leadership depends on the rapidly changing scenario due to revolution. TVET leaders should exploit the potential opportunities brought by the new era with much responsibility and wisdom, by providing flexible leadership for their institutions.